The effect of Health, Safety and Environment (HSE) assurance in logistics organization on the retention of employee(s) in Labuan federal territory: the role of pay satisfaction as a mediator / Dewi Tajuddin ... [et al.] - Tajuddin, Dewi; Kusin, Al Gaffrie Mil; Azwa Ambad, Sylvia Nabila; Hasan, Hamsinar (Universiti Teknologi MARA, 2021)
Safety culture has been described as a critical factor that setting up the importance of safety within an organization. The prevention of work-related accidents is an important measure taken by any company to assure the well-being of their employees and maintaining good working environment. Therefore, health, safety, and (work) environment (HSE) security is a relevant issue to be discussed in terms of employee retention. The objective of this study is to determine the effect of HSE security towards employee retention, with pay satisfaction will be the mediator. This study was adopting a survey research design and a sample of 200 employees of Asian Supply Base Sdn. Bhd. participated as respondents. The collection of data was analysed using Smart-PLS. The results showed that HSE security is positively affecting employee retention, and pay satisfaction have mediating effect on the relationship between HSE security and employee retention.